If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -8y + 9x = 0 Reorder the terms: 7x + 9x + -8y = 0 Combine like terms: 7x + 9x = 16x 16x + -8y = 0 Solving 16x + -8y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8y' to each side of the equation. 16x + -8y + 8y = 0 + 8y Combine like terms: -8y + 8y = 0 16x + 0 = 0 + 8y 16x = 0 + 8y Remove the zero: 16x = 8y Divide each side by '16'. x = 0.5y Simplifying x = 0.5y
| -3*X*X+6X=-1 | | 6q^2+13q-8=0 | | 2(3k+7)=6k-12 | | 3c(2n+3)=2n+21 | | -2x-4y=-20 | | $3.00/hour=cents/minute | | -14x+10x=2(-8-3x) | | 8+3(x-7)=3-6(x-7) | | 3.5x+10.5y=116.5 | | -4(4n+2)=28 | | 18=-5x+2x+3 | | 30+18p=25+20p | | 10=-4.8 | | 11x+16-8x=-56-5x | | 12q^2-35q-3=0 | | (2x+3)*(x^2+6X+11)=0 | | Σ=5/(25n^2-5n-6) | | 2x+8-10x=28-8x | | 3a+b=14 | | 1x+3=4x | | 9(x+10)=5(x+3)+25 | | Tan(7x/12) | | 8x-12=12x-8 | | y=(x-17)(x+2) | | 5x+36=9x | | a/3/5=25/2 | | y=(x-6)(x-6)+2 | | 24=6(-t-3) | | 7x+14=19-(x-11) | | (x+(x+2))+2=12 | | 2.5(x-3.9)=12 | | f=(d) |